Kedokteran dalam Sejarah Islam - Saepudin, Didin (Buletin Al-Turas, 2006)
Medicine is one of the famous science in Islamic Civilization among the others. There are many scholars in thisdiscipline. I.e. al-Razi, Ibn Sina, al-Biruni, and Ibn Rusyd. The islamic medicine has already influenced Europe civili-zation untill 15th century